State of Underheating in Georgia and Estimation of Associated Economic Costs - World Bank (World Bank, Washington, DC, 2021)
The objective of the report is to present the state of the underheating in Georgia and to quantify the economic costs of underheating. It presents estimates of the economic benefits of energy efficiency interventions that reduce underheating in Georgia. It also presents an indicative cost of the country-wide energy efficiency interventions that may lead to improvement of indoor temperature. The rest of this document is structured as follows: section two describes the approach followed for analyzing the impacts and costs to Georgia’s economy of inadequate heating and presents results of the analysis. Section three describes the survey results of underheating in preschools as well as primary and secondary schools. Section four describes the survey results on underheating in health care facilities and private businesses, including small retail convenience stores and tourist guest houses. Section five describes the survey results on underheating in residential buildings. Section six summarizes the results of the surveys and highlights areas for future study or action. The appendices contain additional material on the survey results and methodologies, as well as a list of sources consulted.